PENGARUH ABU TERBANG BATUBARA TERHADAP SIFAT KIMIA TANAH DAN SERAPAN TIMBAL (Pb) OLEH TANAMAN AKAR WANGI (Vetiveria zizanioides L.) - Benediktus Lucky Aditya Nugroho; Nina Dwi Lestari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Coal fly ash is a soil amendment that can be used to improve soil productivity because coal fly ash contains essential nutrients needed by plants. However, coal fly ash also contains heavy metals. This study was at a time to explore the effect of coal fly ash on soil chemical properties and lead uptake by vetiver plant (Vetiveria zizanioides L.). Treatments tested were applications of six proportion levels (0, 2.5, 5., 10, 15, and 30% by weight). The seven treatments were arranged in a completely randomized design with three replicates. The result showed that the coal fly ash had a significant effect on soil pH, total-P, total-N, total-K and Pb. The value of the Pb translocation factor from the roots to the shoot of the vetiver plant was relatively low, so that the vetiver plant was not suitable for use in phytoextraction of Pb from Pb-contaminated soil.